Pemberdayaan Generasi Z Dalam Pengolahan Sampah Organik Untuk Mewujudkan Desa Sehat Ramah Lingkungan - Dewi Rokhmah; Nabila Anisa Toyibah; Nabila Diana Kholidah; Mirza Fairuz Nafis; Rayen Rifaqih; Faza Naila Khoiron (Journal of Community Development, 2023)
Generation Z is able to have great characteristics and potential to improve their environment which has been damaged by individuals who do not want to protect their own environment. Based on data obtained from the 2020 Waste Management Information System (SIPSS), Bondowoso Regency produces 287.18 tonnes/day of waste. Tangsil Kulon Village is one of the villages in Bondowoso Regency which is also a waste producing area. This increase in waste generation can be overcome by processing waste in several ways, one of which is using the help of Black Soldier Fly (BSF) fly larvae, namely maggots. Community empowerment methods are fully implemented in the field, namely using community education and training methods. This activity was carried out in the context of realizing Tangsil Kulon Village as a Healthy, Environmentally Friendly Village, which was carried out through community counseling and empowerment, namely using community education methods and training and direct practice with assistance from activity facilitators. The results of the activity showed that there was an increase in understanding and skills of the first target regarding how to process inorganic waste using the waste bank method, which was 13.99%, then the second regarding processing organic waste with maggots, namely 5.27%, and the third regarding making fertilizer. compost, namely 10.53%